Cutting carbon emissions by using H2 gas on a heavy-duty 2-stroke marine engine - Van Chien Pham; Van Vang Le; Van Si Hoang; Won-Ju Lee; Sujeong Choe; Jae-Hyuk Choi (Journal of International Maritime Safety, Environmental Affairs, and Shipping, 2025)
This study was conducted to determine the optimal hydrogen (H2) content in the fuel gaseous mixture to achieve the goal of cutting carbon emissions to meet the International Maritime Organization’s emission regulations. The mixtures of hydrogen-methane (H2-CH4) with various H2 contents were applied on an existing 2-stroke heavy-duty diesel-CH4 dual-fuel (DF) marine engine. The combustion process and emissions formations inside the engine cylinder were calculated using the computational fluid dynamic (CFD) method with the support of the ANSYS FLUENT software. Experiments were also performed to get experimental results for CFD model validation purposes. The results showed that if the H2 content accounted for 30% of the total fuel mass supplied, the engine’s carbon dioxide (CO2) emissions at load levels of 25%, 50%, 75%, and 100% of the rated load were reduced by 45.73%, 45.86%, 45.90%, 49.08%, respectively. This means that if 30% of the mass of CH4 is replaced by H2 the goal of cutting at least 40% of CO2 emissions will be achieved. In addition, the effect of H2 on other emissions, in-cylinder pressure and temperature, engine performance, etc. was also investigated and presented in this report.